My Three Best Friends and Me, Zulay - Best, Cari; Brantley-Newton, Vanessa (New York : Farrar Straus Giroux, 2015)
"Zulay is a blind girl who longs to be able to run in the race on field and track day at her school"--
Keywords: Blind children -- Juvenile fiction; Children with disabilities -- Juvenile fiction; Friendship in children -- Juvenile fiction; Schools -- Juvenile fiction; Blind -- Fiction; People with disabilities -- Fiction; Friendship -- Fiction; Schools -- Fiction